“Evaluación de dosis de microorganismos benéficos en cultivo de cebolla china (Var. Roja chiclayana), bajo condiciones agroclimáticas del valle Lamas” - Hernández Guevara, Dilver Eli (2014)
The present qualified work of investigation " Evaluation of dose of charitable microorganisms in culture of Chinese onion (allium fistulosum) var. red chiclayana, under conditions agroclimaticas of the valley of Muds ", had as specific aims: To determine the ideal dose of the charitable microorganisms that presents better results in the production of Chinese onion (allium fistolosum), to conditions agroclimáticas in the valley of Muds, To realize the economic analysis of the treatments. lt was established in the Horticultura! Property in the country " The Pacific Ocean ", In the District and province of Muds, (DBCA) was in use the statistical design of Blocks completely at random, with four blocks, five treatments and with a total of 20 experimental units it were EM'S Dose: To=Testigo; T1=1.00 l/ha T2=1.5 l/ha; T3=2.00 l/ha; T4=2.5 l/ha. The most relevant conclusions were that the treatments applied on the basis of the EM-1 indujeron answers in the fresh weight of the plant (cm), Diameter of the stem (cm) and total number of leaves for plant, the same ones who prometed the growth and development structures of the plant, the treatment being translated in major performances in the culture of the Chinese onion, variety to Red chiclayana, 4 (2.5 l/ha) with EM, threw the major average of performance of Of total weight of the plant with 50.63 grams. All the studied treatments generated wealth being the treatment TO (witness) the one that threw the high value of Benefit I cost with 0,47. Keywords: Yield, microorganism, benefit I cost, fresh.